Pendudukan Jepang di Indonesia - Rut, Shintya; Zalukhu, Desveronika; Nazwa, Dirham; Sinaga, Rosmaida (Innovative: Journal Of Social Science Research, 2024)
The Japanese occupation of Indonesia lasted from 1942 to 1945, during World War II. Japan replaced Dutch colonialism and implemented a strict government system. Although initially accepted as liberators from Dutch colonialism, Japanese policies actually caused suffering, including forced labor and extortion of resources. In addition, Japan tried to propagate the idea of Asian nationalism and gather popular support by creating local organizations. This occupation ended after Japan lost the war, which sparked a spirit of independence in Indonesia, ultimately leading to the proclamation of independence on August 17 1945.